2015
DOI: 10.5468/ogs.2015.58.3.183
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial borderline ovarian tumor: Diagnosis and treatment strategy

Abstract: Epithelial borderline ovarian tumors (BOT) are distinctive from benign tumors and carcinoma. They occur in younger women more often than carcinoma, and there is some difficulty making correct diagnosis of BOT. Two subtypes of BOT, serous and mucinous borderline tumor have different characteristics and very different clinical behavior. Serous borderline tumor (SBT) with micropapillary pattern shows more incidence of extra ovarian disease and often coexists with invasive implant. SBT with micropapillary pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 12 publications
(13 reference statements)
1
25
0
2
Order By: Relevance
“…Nevertheless, when we particularly examined whether the surgical type was cystectomy or not (Model B), cystectomy increased the risk of recurrence. This finding is consistent with results from a multi‐center study, systematic reviews and meta‐analysis which showed that cystectomy was a significant risk factor for BOT recurrence …”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, when we particularly examined whether the surgical type was cystectomy or not (Model B), cystectomy increased the risk of recurrence. This finding is consistent with results from a multi‐center study, systematic reviews and meta‐analysis which showed that cystectomy was a significant risk factor for BOT recurrence …”
Section: Discussionsupporting
confidence: 92%
“…IECA is thought to be the further deterioration of MBOTs and precancerous lesions of ovarian cancer. MBOTs, IECA, microinvasive carcinoma, and invasive mucinous carcinoma are thought to be a continuous process . The overall prognosis of patients with MBOTs is excellent.…”
Section: Introductionmentioning
confidence: 99%
“…MBOTs, IECA, microinvasive carcinoma, and invasive mucinous carcinoma are thought to be a continuous process. 3,4 The overall prognosis of patients with MBOTs is excellent. It was reported that the 5-year survival rate of MBOTs was up to 90% or even higher.…”
Section: Introductionmentioning
confidence: 99%
“…Histopathologically, this group of neoplasms exhibit behaviour that is intermediate between benign cyst-adenomas and invasive carcinomas. Two subtypes of BOTs, serous and mucinous borderline tumors are more common and have different characteristics as well as different clinical behaviour 8,9. Rarely other types like endometroid, clear-cell or transitional cell (Brenner) borderline tumors are also present 10…”
Section: Introductionmentioning
confidence: 99%